2015
DOI: 10.1515/bmc-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Metal bridges to probe membrane ion channel structure and function

Abstract: Ion channels are integral membrane proteins that undergo important conformational changes as they open and close to control transmembrane flux of different ions. The molecular underpinnings of these dynamic conformational rearrangements are difficult to ascertain using current structural methods. Several functional approaches have been used to understand two- and three-dimensional dynamic structures of ion channels, based on the reactivity of the cysteine side-chain. Two-dimensional structural rearrangements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 132 publications
1
12
0
Order By: Relevance
“…Cd 2+ inhibition of cysteine-substituted channels can demonstrate the close vicinity of the substituted residues because Cd 2+ binding requires multiple cysteines (29, 30). We had to apply Cd 2+ to the N-terminal cysteine mutants from the intracellular side, that is from the pipette.…”
Section: Resultsmentioning
confidence: 99%
“…Cd 2+ inhibition of cysteine-substituted channels can demonstrate the close vicinity of the substituted residues because Cd 2+ binding requires multiple cysteines (29, 30). We had to apply Cd 2+ to the N-terminal cysteine mutants from the intracellular side, that is from the pipette.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we performed double-cysteine substitutions to the third Ca 2+ site and sought to assess whether the transition metal ion Cd 2+ could form a metal bridge between TM2 and TM10 and how such restricting their conformation would impact channel activation. The readily reversible formation of Cd 2+ metal bridge permits temporal probing of the effects from crosslinking TM2 and TM10 on channel activity (Linsdell, 2015). By screening different TM2-TM10 interhelical pairs of cysteines, we found that application of Cd 2+ (0.5, 1, or 10 mM) largely abolishes channel activity of the double mutant E425C/D879C, but not WT or the single-cysteine mutants E425C and D879C, even under saturating 100 mM Ca 2+ (Figures 6A-6E).…”
Section: Tm2-tm10 Interaction Can Strongly Influence Tmem16a's Channel Gatingmentioning
confidence: 99%
“…For this reason, it has been suggested that engineered disulfide bonds can "trap" residues into rare and otherwise unnatural conformations (12). To better understand the kinetics of the C110 -C892 linkage, we used acute applications of the soft metal cadmium, as successfully used to probe cysteine proximity in previous studies of CFTR (12,24,42) and many other types of ion channels, to perform metalbridging experiments. To ensure that engineered cysteine residues of these channels were free to coordinate cadmium, the cells were preincubated with 1 mM DTT directly before channel activation.…”
Section: D110c/k892c-cftr Channels Coordinate Cadmium Which Inhibits Channel Macroscopic Conductancementioning
confidence: 99%